PENGARUH GAYA KEPEMIMPINAN PARTISIPASI DAN MOTIVASI KERJA TERHADAP KINERJA GURU PADA SDN GUGUS III BALIKPAPAN UTARA - jurnalmap map; Sugiarti ÔÇì; Nugroho Mardi Wibowo; Cathrine Sri Hartati (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
ABSTRACT This study aims to describe the participatory leadership style, motivation and performance of teachers in SDN Gugus III North Balikpapan and to analyze leadership performance and performance together on teacher performance in SDN Gugus III North Balikpapan. This study uses a quantitative approach and type of explanatory research. The population in this study were all teachers of SDN Gugus III North Balikpapan. The study sample was interviewed by 53 teachers. The sampling technique uses saturated samples. The method uses data using a questionnaire. Descriptive data analysis methods and multiple regression analysis, F test and t test. The results of the study showed participative leadership style and work motivation positively on the performance of teachers in North Balikpapan Elementary School III. Participatory leadership style and morale work motivation on the performance of teachers in SDN Gugus III North Balikpapan Keywords: participatory leadership style, work motivation, teacher performance